Hollow cobalt-based microtube designed based on skin depth theory and preparation method and application thereof
By designing hollow cobalt-based microtubes based on skin depth theory, the problems of insufficient magnetic loss and high fill ratio in existing microwave absorbing materials at low frequencies have been solved, achieving high-efficiency microwave absorption at ultra-thin and ultra-low fill ratios, meeting the requirements of lightweight and broadband absorption.
Patent Information
- Application Number
- CN202511249733.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-09-03
- Publication Date
- 2025-12-09
AI Technical Summary
Existing microwave absorbing materials suffer from insufficient magnetic loss in the low-frequency band, and high fill ratios or large thicknesses lead to excessive system loads. Furthermore, the lack of theoretically guided electromagnetic wave absorbing microtube structure design makes it impossible to achieve efficient absorption in a wide low-frequency band.
Hollow cobalt-based microtubes were designed based on skin depth theory. By precisely controlling the wall thickness of the microtubes to the skin depth level, and combining their unique hollow structure, efficient absorption of electromagnetic waves and lightweight applications were achieved.
With ultra-thin thickness and ultra-low fill ratio, hollow cobalt-based microtubes exhibit excellent microwave absorption performance within a wide low-frequency absorption bandwidth, meeting the requirements of lightweight and wideband absorption, achieving a minimum reflection loss ≤-37 dB and an effective absorption bandwidth ≥5.4 GHz.
Smart Images

Figure CN121099592A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of electromagnetic wave absorbing materials technology, specifically to a one-dimensional hollow cobalt-based microtube (HCMT) material whose wall thickness is precisely controlled by the skin depth theory, its preparation method, and its application in high-performance low-frequency microwave absorption. Background Technology
[0002] With the rapid development of modern electronic devices, high frequency and integration have become important trends in technological progress. However, this trend has also brought about low-frequency electromagnetic pollution, especially in the 2-10 GHz frequency band. This pollution has become a major factor interfering with the normal operation of precision instruments, leaking sensitive information, and posing potential threats to human health. Therefore, there is an urgent need to develop a new type of microwave absorbing material. This material not only needs to be ultra-thin (less than 3 mm) and have an extremely low filler ratio (less than 5% by weight), but also needs to provide a wide low-frequency absorption bandwidth to achieve efficient electromagnetic wave absorption.
[0003] However, traditional solutions have encountered fundamental bottlenecks in addressing this challenge. For example, magnetic materials such as ferrites exhibit a sharp decline in magnetic loss performance in the S-band and C-band frequency ranges, resulting in minimum reflection loss (RLmin) typically exceeding -20 dB. While carbon-based composites, such as porous carbon fibers or magnetic particle / carbon nanotube composites, can enhance interfacial polarization through their unique hollow structure, achieving effective absorption usually requires a high filler ratio, approximately 20 to 35 wt%, or a substantial material thickness exceeding 5 mm. For instance, nickel-coated multi-walled carbon nanotubes (Ni@MWCNTs) reported in the literature achieve a minimum reflection loss of -33 dB with only 0.5 wt%, while iron / silicon carbide fibers require 35 wt% plus a thickness of 2.25 mm to achieve a minimum reflection loss of -46.3 dB. These high filler ratios and excessive thickness requirements severely limit the potential of these materials in lightweight applications.
[0004] More importantly, the design of existing microwave absorbing materials often relies on empirical trial-and-error methods, lacking a deep understanding of the relationship between material characteristic dimensions and the physical mechanisms of electromagnetic wave attenuation. Although the skin depth (δ) theory indicates that eddy current loss can be maximized when the conductor wall thickness is close to the skin depth (for example, the skin depth of cobalt is 0.33-1.2 micrometers in the 1-18 GHz band), this theory has not yet achieved a breakthrough in the design and engineering application of high-performance microwave absorbers due to the technical difficulties in precisely controlling the submicron wall thickness, the poor stability of hollow structures at high temperatures, and the insufficient synergy among various loss mechanisms. Summary of the Invention
[0005] The purpose of this invention is to address the problems of insufficient magnetic loss in the low-frequency band (2-4 GHz), excessive system load due to high filler ratio (>20 wt%) or large thickness (>5 mm) of existing microwave absorbing materials, and the lack of theoretical guidance for the design of electromagnetic wave absorbing microtube structures. The invention provides a hollow cobalt-based microtube designed based on skin depth theory, its preparation method and application.
[0006] To address the aforementioned challenges, this invention proposes a hollow cobalt-based microtube designed based on skin depth theory. The aim is to achieve efficient electromagnetic wave absorption and lightweight applications by precisely controlling the wall thickness of the microtube to the skin depth level, combined with its unique hollow structure. This microtube not only possesses an ultra-thin thickness (<3 mm) and an ultra-low filler ratio (<5 wt%), but also exhibits excellent microwave absorption performance over a wide low-frequency absorption bandwidth.
[0007] Specifically, this invention utilizes advanced material preparation technology to successfully fabricate cobalt-based microtubes with wall thickness precisely controlled within the skin depth range. The hollow structure of these microtubes not only enhances the interfacial polarization effect but also promotes multiple reflections and scatterings of electromagnetic waves within the material, thereby improving the attenuation efficiency of electromagnetic waves. Simultaneously, the cobalt-based material itself possesses high magnetic loss capability, maintaining good magnetic loss characteristics in the S / C band, further enhancing the material's microwave absorption performance.
[0008] Furthermore, this invention delves into the relationship between material characteristic dimensions and the physical mechanism of electromagnetic wave attenuation, revealing the crucial role of skin depth theory in the design of high-performance microwave absorbers. By optimizing parameters such as the wall thickness, length, and arrangement of microtubes, this invention achieves precise control over electromagnetic wave absorption performance, providing strong theoretical support and experimental evidence for the development of novel, highly efficient microwave absorbing materials.
[0009] This invention focuses on resolving three core contradictions: First, the imaginary part μ" of the permeability of traditional magnetic materials such as ferrites decreases sharply to below 0.5 in the S / C band, making it difficult to break through -20 dB in reflection loss; second, although carbon-based composite materials can enhance interfacial polarization through hollow structures, current related technologies show that (e.g., Fe / SiC hybrid fibers require a 35 wt% filling ratio and a thickness of 2.25 mm to achieve -46.3 dB), making it impossible to achieve both lightweight and strong absorption performance; most importantly, existing technologies completely ignore the skin depth (δ), a physical parameter that determines the depth of electromagnetic wave attenuation in a conductor, resulting in a disconnect between the design of the hollow structure wall thickness and the electromagnetic response mechanism, making it impossible to maximize eddy current loss efficiency by precisely controlling the wall thickness to the δ level.
[0010] The present invention discloses a hollow cobalt-based microtube with skin depth control, wherein the hollow cobalt-based microtube is a one-dimensional hollow tubular structure with an aspect ratio ≥100 and a wall thickness of 0.28~0.38 μm; the wall is composed of a continuous phase of metallic cobalt; and the surface of the wall is coated with composite reduced graphene oxide nanosheets by electrochemical deposition, with a graphene oxide nanosheet coverage of ≥80%.
[0011] The tube wall thickness of this invention matches the skin depth of cobalt in the 1-18 GHz frequency band, enabling efficient microwave attenuation within the tube wall. The tube wall, composed of a continuous cobalt phase, forms a continuous conductive channel, promoting the synergistic effect of eddy current loss and dielectric loss. When the graphene oxide coverage is greater than or equal to 80%, it enhances interfacial polarization loss and couples with the eddy current loss of cobalt, thereby broadening the absorption bandwidth.
[0012] Furthermore, the tube wall thickness is 0.28~0.38 μm, which matches the skin depth of cobalt in the 1-18 GHz frequency band (i.e., the tube wall thickness is close to the theoretical value of the skin depth of cobalt in this frequency band, ensuring that microwave energy is fully attenuated in the tube wall and avoiding penetration or reflection loss).
[0013] The present invention relates to a hollow cobalt-based microtube with skin depth modulated for microwave absorption as a microwave absorbing material.
[0014] Furthermore, the microwave absorbing material is composed of hollow cobalt-based microtubes and a polymer matrix (including traditional microwave absorbing media such as paraffin, epoxy resin, and silicone rubber, whose main functions are dispersion and load-bearing). The filling ratio of the hollow cobalt-based microtubes is between 0.5 and 0.85% by weight (wt%). The thickness of the microwave absorbing material is set in the range of 1.0 to 3.0 mm, which matches the absorption frequency band and aims to improve the broadband absorption performance of the material.
[0015] Furthermore, the microwave absorbing material meets at least one of the following requirements in the 2-18 GHz frequency band: the filler mass ratio of hollow cobalt-based microtubes with skin depth modulation is less than 1 wt.%, the effective absorption bandwidth is ≥5.4 GHz (covering the mainstream radar frequency band), and the minimum reflection loss is ≤-37 dB (achieving strong energy attenuation). This solves the technical problems of traditional absorbing materials such as "large filler, narrow bandwidth, and low loss", while meeting the requirements of lightweight, wide bandwidth, and high attenuation in scenarios such as stealth of high-speed aircraft.
[0016] Furthermore, the microwave absorbing material is used to prepare stealth skin for aircraft.
[0017] Furthermore, the stealth skin of the aircraft is coated on the surface of a metal substrate, with a coating thickness of 2.0~3.0 mm.
[0018] A method for preparing hollow cobalt-based microtubes with skin-touch depth modulation according to the present invention:
[0019] (a) Electrodeposition: Using carbon fiber as the cathode, in an electroplating bath containing 0.23–0.25 g / mL CoCl₂·6H₂O and 0.25–0.35 mg / mL GO, at 58–62°C and a current density of 0.18–0.22 A·dm³. -2 Electroplating for 8.0~10 min forms the Co / rGO / CF precursor;
[0020] (b) Gradient heat treatment:
[0021] Oxidation: In an air atmosphere, the Co / rGO / CF precursor was heated to 790~810°C at a rate of 5°C / min and held at that temperature for 40~50min for oxidation treatment;
[0022] Reduction: In an Ar / H2 mixed atmosphere, the temperature is lowered to 490~510°C at 10°C / min and held for 20~40 min to carry out reduction treatment.
[0023] In this invention, GO (graphene oxide) is used as a dispersant and structure directing agent. Its concentration affects the coating uniformity and the carbon template removal efficiency during the heat treatment stage. An appropriate amount of GO can inhibit the agglomeration of cobalt particles.
[0024] The electrodeposition time (8-10 min) setting of this invention is achieved by precisely controlling the product of current density and time (electric charge) to initially regulate the final coating thickness. This is a key prerequisite for obtaining the target skin depth (approximately 1-5 μm) (Note: Skin depth is related to the material's electrical conductivity, magnetic permeability, and electromagnetic wave frequency. Elemental cobalt can achieve efficient absorption under these parameters).
[0025] The electrical conductivity of elemental cobalt (σ≈1.4×10⁻⁶) 7The permeability (μ≈250) and the skin depth of the microtube in the GHz band are about 2-3 μm. By controlling the wall thickness of the microtube within this range through the above process, the electromagnetic wave energy can be efficiently dissipated in the tube wall, avoiding penetration loss or reflection loss, and achieving an absorption efficiency of nearly 100%.
[0026] The oxidation stage of this invention involves setting a heating rate (5℃ / min) and an oxidation temperature (790~810℃). Slow heating prevents rapid decomposition of the carbon fiber template, which could lead to the collapse of the tubular structure. High-temperature oxidation achieves a dual purpose:
[0027] 1) Remove the carbon fiber and graphene template to form hollow channels;
[0028] 2) Cobalt is converted into oxides such as Co3O4, providing a controllable precursor for subsequent reduction steps. Temperatures below 790℃ may result in template residue, while temperatures above 810℃ may easily cause cobalt oxide volatilization or grain coarsening.
[0029] In the reduction stage of this invention, the cooling rate (10℃ / min) and reduction temperature (490~510℃) are set to rapidly cool down and suppress excessive grain growth. 490-510℃ is the thermodynamically optimal range for the reduction of Co3O4 to elemental cobalt. An Ar / H2 atmosphere is used to prevent secondary oxidation of cobalt, ensuring the formation of high-purity elemental cobalt. If the temperature deviation exceeds ±20℃, non-target products such as CoO or Co(OH)2 may be generated.
[0030] The hollow structure of this invention is achieved by: after removing the carbon fiber template in the oxidation stage, the elemental cobalt formed in the reduction stage naturally forms a hollow tubular structure. Thickness control: the electrodeposition parameters determine the precursor thickness, and the volume change coefficient during the heat treatment process (approximately 15-20%) can be calibrated through pre-experimentation, ultimately achieving micron-level wall thickness precision control.
[0031] Further oxidation: In an air atmosphere, the Co / rGO / CF precursor was heated to 800°C at a rate of 5°C / min and held at that temperature for 40-50 min for oxidation treatment;
[0032] Reduction: The oxidized Co / rGO / CF precursor was subjected to reduction treatment in an Ar / H2 mixed atmosphere, cooled to 500°C at a rate of 10°C / min, and held for 20-40 min.
[0033] Furthermore, the electroplating solution also contains C at a mass concentration of 0.04~0.06 wt%. 18 H 29 NaO3S, 0.0025~0.0035 g / mL C6H5NaO2S; pH value maintained at 4.2~4.8.
[0034] The present invention has the following beneficial effects:
[0035] The hollow cobalt-based microtubes of this invention achieve a triple breakthrough in performance: First, at an ultra-low filler ratio of 0.85 wt%, a 1.0 mm thick coating achieves a minimum reflection loss of -37.89 dB in the S-band (3.45 GHz), which is significantly lower than that of Ni@MWCNTs materials of the same thickness (0.5 wt% RL) reported in the literature. min Firstly, the effective absorption bandwidth (EAB, RL≤-10 dB) is increased by more than 15%, completely overturning the traditional understanding that "strong absorption at low frequencies requires high load." Secondly, when the thickness increases to 3.0 mm, the effective absorption bandwidth (EAB, RL≤-10 dB) is broadened to 7.8 GHz (4.2-12.0 GHz), covering multiple frequency bands of C / X / Ku, which is 144% higher than the 3.2 GHz bandwidth of Fe / SiC fiber. Thirdly, through radar cross section (RCS) simulation verification, the aircraft model coated with HCMT has a RCS value reduction of ≥10 dBsm in the entire frequency band of 3-18 GHz, especially maintaining a suppression rate of 9.6 dBsm in the 18 GHz high-frequency band, providing lightweight (density <1.2 g / cm³) for aerospace stealth equipment. 3 A revolutionary solution for thin-film (<3 mm) and wideband compatibility. Attached Figure Description
[0036] Figure 1 : HCMT fabrication flowchart (electrodeposition → thermal oxidation → reduction); (Hollow cobalt-based microtube (HCMT) fabrication flowchart based on skin depth. The left side shows the skin depth curve of cobalt in the 1-18 GHz band, showing a minimum skin depth of 0.33 μm; the right side shows the fabrication steps: using carbon fiber as a template, a Co / rGO / CF precursor is formed by electrodeposition, followed by gradient thermal treatment (oxidation and template removal at 800℃ in air atmosphere, reduction in Ar / H2 atmosphere) to obtain a hollow structure, intuitively presenting the core logic of "skin depth guiding structural design")
[0037] Figure 2SEM images of Co / rGO / CF precursor (ac) and HCMT (df) (wall thickness: 0.18 μm → 0.33 μm); (SEM images and EDS elemental distribution of Co / rGO / CF precursor and HCMT; (ac) shows Co / rGO / CF with different electroplating times, indicating that the coating thickness increases with time (0.18 μm → 0.32 μm → 0.55 μm), exhibiting a one-dimensional core-shell structure; (df) shows HCMT after heat treatment, with the wall thickness slightly reduced due to redox reaction (0.1 μm → 0.14 μm → 0.33 μm), forming a complete hollow tube; (gj) EDS confirms the uniform distribution of Co, C, and O elements, verifying the composition and structure of the hollow cobalt-based microtube)
[0038] Figure 3 RL curves (frequency response for thicknesses of 1.0–5.0 mm) of Co / rGO / CF-5, Co / rGO / CF-7, and Co / rGO / CF-9; (Reflection loss (RL) curves of the Co / rGO / CF series; showing the absorption performance of samples with different plating times: Co / rGO / CF-5 (5 min) RLmin=-19.2 dB, EAB=3.0 GHz; Co / rGO / CF-7 (7 min) has the best performance (RLmin=-25.3 dB, EAB=3.98 GHz); Co / rGO / CF-9 (9 min) has a decreased performance due to excessive coating thickness (super-skin depth) (RLmin=-11.3 dB, EAB=1.2 GHz, confirming that the coating thickness needs to match the skin depth)
[0039] Figure 4 RL curves (frequency response for thicknesses of 1.0-5.0 mm) of HCMT-5, HCMT-7, and HCMT-9; (Reflection loss (RL) curves of the HCMT series; the hollow structure significantly improves performance: HCMT-5 (0.1 μm) RLmin=-39.0 dB, EAB=7.8 GHz; HCMT-7 (0.14 μm) performance declines; HCMT-9 (0.33 μm, matching skin depth) is optimal, with RLmin≈-40 dB and EAB=5.5 GHz at a thickness of 1.0 mm, and low-frequency RLmin≈-37.1 dB at a thickness of 3.0 mm, demonstrating the key role of wall thickness matching skin depth)
[0040] Figure 5 Electromagnetic parameter curves of HCMTs-5 and Co / rGO / CFs;
[0041] Figure 6: RCS simulation results of HCMT-9 (compared to PEC-coated aircraft) (Figure a) and schematic diagram of skin effect and multiple loss mechanism (conductive loss + interface polarization + magnetic loss) (Figure b); (Radar cross section (RCS) simulation and absorption mechanism schematic diagram; (a) shows that the HCMT-9 coating reduces the RCS of the aircraft model by 12-15 dBm. 2 (a) Verify its practical application value; (b) Reveal the differences in electric field loss at different frequencies; (c) Illustrate the multi-loss mechanism: conductive network loss, skin effect thermal conversion, multiple reflections in hollow structures, and interface polarization, demonstrating the synergy between structure and mechanism. Detailed Implementation
[0042] To make the objectives, technical solutions, and advantages of the embodiments of the present invention clearer, the spirit of the contents disclosed in the present invention will be described in detail below. After understanding the embodiments of the present invention, any person skilled in the art can make changes and modifications based on the technology taught in the present invention without departing from the spirit and scope of the present invention.
[0043] The illustrative embodiments and descriptions of the present invention are used to explain the present invention, but are not intended to limit the present invention.
[0044] Example 1
[0045] This embodiment presents a method for preparing hollow cobalt-based microtubes based on skin depth theory:
[0046] 1. Skin depth-guided precise structure construction:
[0047] Electrodeposition: Cobalt source was provided by CoCl2·6H2O (0.24±0.01 g / mL), and GO (0.3±0.05 mg / mL) was used as a pre-composite dielectric phase; Additives: Sodium dodecylbenzenesulfonate (0.05±0.01 wt%) was used to disperse GO (to avoid agglomeration and ensure uniform coating of rGO in the subsequent process), and sodium benzenesulfinate (0.003±0.0005 g / mL) was used to optimize cobalt crystallization (to construct a continuous cobalt metallic phase, providing a continuous conductive channel for eddy current loss); Temperature was controlled at 60±2℃, and A·dm³ was controlled at 0.2±0.02 A·dm³. -2 Current and time of 9.0 ± 0.5 min were used to ensure that Co / rGO was uniformly co-deposited on the carbon fiber template to form a precursor with a uniform structure.
[0048] Oxidation step (800±10℃, 45±5 min): Ablation of carbon fiber template, while partially oxidizing the Co surface layer to construct a hollow tubular prototype;
[0049] Reduction step (Ar / H2 atmosphere, 500±10℃, 30±5 min): Reduce Co oxide to a continuous metallic phase, stabilize rGO (avoid high-temperature graphitization), and finally obtain hollow cobalt-based microtubes (HCMTs) with a wall thickness of 0.28~0.38 μm (matching the skin depth of cobalt at 1~18 GHz), an aspect ratio ≥100, and an rGO coverage ≥80%.
[0050] Existing technologies mostly use solid particles (random wall thickness, easy microwave reflection / penetration) and have uneven structures (rGO agglomeration, cobalt phase fracture, and disordered loss mechanisms). This invention achieves efficient microwave attenuation within the tube wall through "quantitative wall thickness" (skin depth matching) and synergistic use of multiple loss mechanisms (continuous cobalt phase supporting eddy currents, and rGO introducing dielectric).
[0051] 2. Coordinated control of electromagnetic parameters:
[0052] Based on the skin depth to obtain the most efficient absorber, this invention minimizes the HCMT filling ratio (0.5~0.85wt%) and material thickness (1.0~3.0 mm) and optimizes the complex permittivity / magnetic constant matching to achieve highly efficient microwave absorption with extremely low filling through quantitative control.
[0053] Figure 1 , 2The preparation process of Co / rGO / CF precursor and HCMT, along with SEM images and EDS elemental distribution analysis, are presented. (a), (b), and (c) show Co / rGO / CF samples after electroplating for 5, 7, and 9 minutes, respectively. A one-dimensional core-shell structure is visible on the carbon fiber surface. The coating thickness increases with electroplating time, reaching 0.18 μm, 0.32 μm, and 0.55 μm, respectively. The hydroxyl and carboxyl functional groups on the graphene oxide (GO) surface adsorb cobalt particles through electrostatic interaction, preventing their aggregation and allowing the coating to gradually fuse into a dense, uniform, and continuous shell, verifying the controllability of the coating thickness. (d), (e), and (f) show HCMT samples after gradient heat treatment. Due to the influence of the redox process, the wall thickness is slightly reduced. The wall thicknesses of HCMT-5, HCMT-7, and HCMT-9 are 0.1 μm, 0.14 μm, and 0.33 μm, respectively, successfully forming a hollow tubular structure. EDS elemental mapping (gj) showed that cobalt (Co), carbon (C), and oxygen (O) were uniformly distributed in HCMT, and XRD analysis confirmed the composition of the hollow cobalt-based microtubes. This hollow structure not only increases the microwave transmission path and loss interface but also reduces the filling ratio, laying a structural foundation for high-efficiency microwave absorption performance. HCMT exhibits a complete hollow tubular shape with uniform wall thickness (fitting the skin depth design), and the rGO nanosheets are tightly encapsulated without agglomeration—proving the effectiveness of "quantitative structural design + precise preparation," providing a physical basis for eddy current loss (continuous cobalt phase) + dielectric loss (rGO interface / defect polarization).
[0054] Figure 3The reflection loss (RL) curves of Co / rGO / CF-5, Co / rGO / CF-7, and Co / rGO / CF-9 are presented, including one-dimensional, two-dimensional, and three-dimensional spectra, reflecting the absorption performance of the precursors under different plating times. Co / rGO / CF-5 (plated for 5 minutes) exhibits a minimum reflection loss (RLmin) of -19.20 dB at 5.95 GHz, and with a thickness of 5.0 mm, an effective absorption bandwidth (EAB, RL≤-10 dB) of 3.0 GHz, covering the 4.5–6.5 GHz and 15.8–16.8 GHz frequency bands. This is attributed to the synergistic effect of magnetic cobalt and reduced graphene oxide (rGO) with excellent conductivity loss. With increasing electroplating time and coating thickness, the electromagnetic coupling and absorption performance of Co / rGO / CF-7 (electroplated for 7 minutes) was further optimized: RLmin reached -25.3 dB at 9.4 GHz, and EAB extended to 3.98 GHz (8.3-12.2 GHz) with a thickness of 2.0 mm. However, coating thickness is not positively correlated with absorption performance; when the thickness exceeds the skin depth of cobalt, the performance actually decreases. Co / rGO / CF-9 (electroplated for 9 minutes) had an RLmin of only -11.3 dB at 9.2 GHz, and EAB of only 1.2 GHz (8.6-9.8 GHz) with a thickness of 2.0 mm, confirming the principle that coating thickness must match the skin depth to achieve efficient absorption. Magnetic loss (dominated by the cobalt continuous phase): The one-dimensional hollow structure extends the electron migration path and enhances eddy current loss (an aspect ratio ≥100 prolongs the eddy current relaxation time and improves loss efficiency).
[0055] Figure 4The reflection loss (RL) curves for HCMT-5, HCMT-7, and HCMT-9 visually demonstrate the improved absorption performance of hollow cobalt-based microtubes after gradient thermal treatment. Compared to the Co / rGO / CF precursor, HCMT exhibits significantly improved minimum reflection loss (RLmin) and effective absorption bandwidth (EAB) due to the formation of the hollow structure and enhanced interfacial polarization effect. HCMT-5 achieves an RLmin of -39.0 dB at 12.20 GHz and an EAB of 7.80 GHz (10.20-18.00 GHz) with a thickness of 3.0 mm, demonstrating broadband absorption capability. With the wall thickness increased to 0.14 μm, the RLmin position of HCMT-7 shifts forward to 10.4 GHz and the EAB narrows to 3.9 GHz (8.3-12.1 GHz) at the same matching thickness, indicating that deviation from the skin depth leads to performance degradation. HCMT-9 exhibits the best performance: with a thickness of only 1.0 mm, RLmin is close to -40 dB, and EAB reaches 5.5 GHz (9.7-15.1 GHz); with a thickness of 2.0 mm, RLmin at 5.8 GHz is -28.0 dB; and with a thickness of 3.0 mm, RLmin at 2.5 GHz is close to -37.1 dB. This confirms that when the microtube wall thickness (0.33 μm) is matched with the skin depth of cobalt, microwaves can penetrate efficiently and be fully absorbed, avoiding both excessive reflection (impedance matching balance) and insufficient absorption (suitable penetration depth), thus achieving excellent microwave absorption performance.
[0056] Figure 5The electromagnetic parameters of the Co / rGO / CF series and HCMT series samples in the 2.0-18.0 GHz frequency band are shown, including the real and imaginary parts of the complex permittivity (εr=ε'-jε'') and complex permeability (μr=μ'-jμ''), exhibiting overall dispersive characteristics. Regarding the real part (ε') of the complex permittivity, the HCMT series is significantly higher than the Co / rGO / CF series: the average ε' of Co / rGO / CF-5 is 4.67, while that of HCMT-5 reaches 11.68, and it further increases with increasing wall thickness (HCMT-9 average 18.58). This is because the carbon fibers in Co / rGO / CF form a shielding layer in the electromagnetic field, hindering effective loss, while the hollow structure of HCMT increases the interface, inducing induced polarization and interfacial polarization effects. The imaginary part (ε'') reflects the loss capability. The ε'' of Co / rGO / CF is below 4, while that of HCMT is between 4 and 10, indicating that the hollow structure significantly improves electromagnetic wave loss efficiency. Regarding complex permeability, both μ' (real part) and μ'' (imaginary part) of HCMT are higher than those of Co / rGO / CF: the μ' of HCMT-9 ranges from 1.61 to 1.13, and μ'' is 0.92 to 0.61, far exceeding the corresponding values of Co / rGO / CF-9. All samples exhibit natural resonance peaks at low frequencies, while HCMT also shows exchanged resonance peaks at high frequencies (e.g., 10 GHz). This is related to the high aspect ratio of the one-dimensional structure generating an additional magnetization field in the alternating electromagnetic field, which helps to form multiple resonance peaks and enhances broadband absorption performance.
[0057] Figure 6 Includes radar cross section (RCS) simulation, electric field loss details, and a schematic diagram of the absorption mechanism, intuitively demonstrating the practical application value and loss principle of HCMT-9. In (a), the RCS curves compare the scattering characteristics of aircraft models coated with HCMT-9, Co / rGO / CF, and uncoated (PEC) in the 3-18 GHz frequency band. The results show that the HCMT-9 coating significantly reduces radar scattering; for example, at 3.0 GHz, the RCS is reduced by approximately 12 dBm compared to PEC. 2 A reduction of approximately 15 dBm at 9.0 GHz 2(a) Verifies its effective suppression capability against electromagnetic wave scattering in real-world scenarios. (b) Electric field loss analysis shows that the HCMT-9 tube wall generates strong electric field attenuation due to its conductive and magnetic loss characteristics. At low frequencies (2.0 GHz), the skin depth is relatively large, and the electric field mainly attenuates at the bottom of the tube; at high frequencies (10.0, 18.0 GHz), the attenuation effect of the tube wall on the electric field is stronger, confirming the influence of the correlation between skin depth and frequency on loss. (c) illustrates its multi-loss mechanism: the conductive network formed by cobalt generates conductive loss through free electron migration; the skin effect enables high-frequency electromagnetic waves to be efficiently converted into heat energy within a 0.33 μm wall thickness; the hollow structure acts as a resonant cavity to extend the wave propagation path and enhance multiple reflections; the polarization effect (interface polarization, dipole polarization) of the Co / rGO heterostructure further enhances the loss, synergistically achieving broadband and efficient wave absorption, reflecting the precise matching between structural design and loss mechanism. Among them, the filling ratio of HCMT (Hollow Cobalt-based Microtube) refers to the mass percentage of HCMT in the composite material. By precisely controlling the filler ratio of HCMT, the electromagnetic and microwave absorption properties of the composite material can be optimized. Meanwhile, the choice of material thickness also significantly impacts absorption performance; an appropriate thickness allows electromagnetic waves to undergo multiple reflections and absorptions within the material, thereby improving absorption efficiency.
[0058] Within the 2-18 GHz frequency band, this composite material exhibits excellent wave absorption performance. The effective absorption bandwidth (EAB, RL≤-10 dB) is ≥5.4 GHz, meaning that within this frequency band, the composite material's reflection loss is less than -10 dB, indicating a high proportion of electromagnetic waves are effectively absorbed. Furthermore, the minimum reflection loss (RLmin) ≤-37 dB further demonstrates that this composite material possesses extremely strong wave absorption capabilities at specific frequencies, capable of converting most incident electromagnetic waves into other forms of energy, thereby achieving highly efficient electromagnetic wave absorption.
Claims
1. A hollow cobalt-based microtube designed based on skin depth theory, characterized in that... The hollow cobalt-based microtubes are one-dimensional hollow tubular structures with an aspect ratio ≥100 and a wall thickness of 0.28~0.38 μm. The surface of the tube wall is covered by electrochemical deposition of reduced graphene oxide nanosheets with a graphene oxide nanosheet coverage of ≥80%.
2. The hollow cobalt-based microtube designed based on skin depth theory according to claim 1, characterized in that, The wall thickness of the tube is 0.30~0.35μm.
3. The application of a hollow cobalt-based microtube designed based on skin depth theory as described in claim 1 or 2, characterized in that, The hollow cobalt-based microtubes described herein serve as microwave absorbing materials.
4. The application according to claim 3, characterized in that, The microwave absorbing material comprises skin depth-controlled hollow cobalt-based microtubes and a polymer matrix; wherein the skin depth-controlled hollow cobalt-based microtubes have a filling ratio of 0.5~0.85wt%; and the thickness of the microwave absorbing material is 1.0~3.0mm.
5. The application according to claim 3, characterized in that, The microwave absorbing material meets at least one of the following requirements in the 2-18 GHz frequency band: the filler mass ratio of hollow cobalt-based microtubes with skin depth modulation is less than 1 wt.%, the effective absorption bandwidth is ≥5.4 GHz, and the minimum reflection loss is ≤-37 dB.
6. The application according to claim 3, characterized in that, The microwave absorbing material is used to prepare stealth skin for aircraft.
7. The application according to claim 6, characterized in that, The stealth skin of the aircraft is coated on the surface of a metal substrate, with a coating thickness of 2.0~3.0 mm.
8. A method for preparing a hollow cobalt-based microtube designed based on skin depth theory as described in claim 1, characterized in that, The preparation method is carried out according to the following steps: (a) Electrodeposition: Using carbon fiber as the cathode, in an electroplating bath containing 0.23–0.25 g / mL CoCl₂·6H₂O and 0.25–0.35 mg / mL GO, at 58–62°C and a current density of 0.18–0.22 A·dm³. -2 Electroplating for 8.0~10 min forms the Co / rGO / CF precursor; (b) Gradient heat treatment: Oxidation: In an air atmosphere, the Co / rGO / CF precursor was heated to 790~810°C at a rate of 5°C / min and held for 40~50 min for oxidation treatment; Reduction: The oxidized Co / rGO / CF precursor was subjected to reduction treatment in an Ar / H2 mixed atmosphere, cooled to 490~510°C at 10°C / min, and held for 20~40 min.
9. The method for preparing hollow cobalt-based microtubes based on skin depth theory according to claim 8, characterized in that, The gradient heat treatment: Oxidation: In an air atmosphere, the Co / rGO / CF precursor was heated to 800°C at a rate of 5°C / min and held at that temperature for 40-50 min for oxidation treatment; Reduction: The oxidized Co / rGO / CF precursor was subjected to reduction treatment in an Ar / H2 mixed atmosphere, cooled to 500°C at a rate of 10°C / min, and held for 20-40 min.
10. The method for preparing hollow cobalt-based microtubes based on skin depth theory according to claim 8, characterized in that, The electroplating solution also contains C at a mass concentration of 0.04~0.06 wt%. 18 H 29 NaO3S, 0.0025~0.0035 g / mL C6H5NaO2S; pH value maintained at 4.2~4.8.